Komorbiditas Depresi dengan Penyakit Fisik Menahun - Idaiani, Sri; Bisara, Dina (Pusat BTDK, 2009)
Depression is frequently comorbid with disease-chronic physical illness. This condition increases the burden of disease to both the individual and his family. The main objective of this study was to understand the relationship between depression and chronic physical illness.This study was a secondary data analysis derived from National Health Survey or Survei Kesehatan Nasional (Surkesnas) 2004. Cluster sampling method was used to select the subjects. The number of subject were 3,722 men and 4,479 women, aged more than 15 years, taken from 10,000 households in 30 selected provinces in Indonesia. In each household 1 person was selected using the Kish tables. The number of samples was proportional to size of population of each province. Symptoms of depression were asked to the subject through interviews with questionnaire Subject was being asked about, the symptoms of depression experienced in the last 2 weeks and 1 year. Prevalence of depression experienced in the last 1 year in the community was 15.53%; the prevalence of depression experienced in the last 2 weeks was 10.3%. There was association between arthritis, heart disease, and asthma to depression. Heart disease had the strongest relation with depression experienced in the last 1 year (OR 3.1). The more disease experienced, the more likely a depression occurred in the last 1 year. It required a screening and disease management toward to prevent higher burden of disease. Â Key words:Â depression, comorhidity, chronic physical illness.